Commentary on association of glycemic index and glycemic load with type 2 diabetes, cardiovascular disease, cancer, and all‐cause mortality - Hsieh, Yi‐Ting; Chou, Ting‐An; Jiang, Yi‐Der (Journal of diabetes investigation, 2024)
High glycemic index/load is associated with type 2 diabetes, cardiovascular disease, cancer, and total mortality. The impact on the Asian population may be higher.